Electronic Type and Diameter Dependence of the Intersubband Plasmons of Single‐Wall Carbon Nanotubes. (5th December 2021) - Wang, Futian; Yang, Dehua; Li, Linhai; Liu, Yumin; Wei, Xiaojun; Zhou, Weiya; Kataura, Hiromichi; Liu, Huaping; Xie, Sishen
Abstract: The intersubband plasmons (ISBPs) of single‐wall carbon nanotubes (SWCNTs) endow SWCNT‐based optoelectronic devices with more functions. However, the structural dependence of the ISBPs of SWCNTs is not fully understood. Here, the effect of electronic types and diameters of SWCNTs on the energy and intensity of their ISBPs is investigated systematically. The results show that the ISBP energy of semiconducting SWCNTs is ≈50–250 meV larger than that of metallic SWCNTs with the same diameters, while the ISBP integral intensity is approximately 1.25 to 4 times stronger. Diameter dependence of ISBPs for both semiconducting and metallic SWCNTs is also observed. With a decrease in diameter, the ISBPs shift to higher energies, while the intensity decreases dramatically. When the diameter is reduced to less than 1 nm, the ISBPs become unobservable. Interestingly, the energy separation between the ISBPs and interband transition S22 (M11 ) decreases with an increase in diameter. Theoretical calculations show that the structure‐dependent ISBP characteristics are dominated by the electronic states of SWCNTs. Based on the ISBP characteristics of different SWCNTs, high‐performance SWCNT‐based near‐infrared electrochromic devices are fabricated by mixing small‐diameter metallic SWCNTs with semiconducting SWCNTs due to their high conductivity and negligible ISBP signals. Abstract : The intersubband plasmons (ISBPs) of single‐wall carbon nanotubes (SWCNTs) are strongly dependent on their electronic types and diameters. The ISBP energy of semiconducting SWCNTs is ≈50–250 meV larger than that of metallic SWCNTs with the same diameters, while the ISBP integral intensity is approximately 1.25 to 4 times stronger. With a decrease in diameter, the ISBPs shift to higher energies, while the intensity decreases dramatically.